Study on the Post Tsunami Impact on Sea Water in Tuticorin Coastal Area - HEMA, S. (Asian Journal of Chemistry, 2010)
This paper deals with the study on the post Tsunami impact on sea water intrusion in Tuticorin coastal area. In the present investigation, more than 12 ground water samples were collected from the various parts of Tuticorin coastal area i.e., 1 and 5 km away from the sea shore. physico- chemical parameters such as pH, alkalinity, turbidity, electrical conductivity, total dissolved solids, total hardness, calcium, magnesium, dissolved oxygen, biological oxygen demand, chemical oxygen demand, fluoride, chlorides, nitrates, ammonia, phosphate, trace metals like iron and manganese were analyzed. Bacteriological examinations for the enumeration of coliform bacteria were carried out. Standard methods were followed for the analysis of physico-chemical and bacteriological examinations. The results were observed in each sample and compared with standards WHO, ICMR and BIS. The water quality in all the areas surveyed was found to be unfit for human consumption. Because of lack of poor water quality due to sea water intrusion, the residents of Tuticorin coastal area were affected by water borne diseases. Hence, suitable water quality management is essential to avoid contamination.